Pengaruh Variasi Putaran Mesin Terhadap Unjuk Kerja Mesin Pencacah Plastik - Nuardi, Ahmad Rito; Qiram, Ikhwanul; Mukhtar, Anas (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2019)
This research is using plastic material with large size into the place of the counting, the material is torn, pulled, crushed, and crushed by two cylinders composed of a knife or spinning the crusher in the opposite direction and material becomes Soft. By adjusting the engine round variation of 200, 300 and 400 rpm and variations of plastic material in the form of rice containers are made of intact and perforated. Thus obtained results that resemble plastic beans for recycled materials. Results of research data on the influence of the variation of the engine rounds on the performance of plastic counting machine, with the change in the results of the difference in the RPM is influenced by the smaller the number (6.68) then the size of the shape at the speed RPM 200. Instead in a large rpm, the weight change of the results of the number (12.6) of the size of the shape at the speed of 400 rpm in whole plastic material.